FACTORS INFLUENCING THE BEHAVIOR OF PALM TREE FARMERS TO ADOPT PHEROMONE TRAPS TO CONTROL LESSER DATE MOTH IN IRAQ - Ali, Mohammed; Kadhim, Zuhal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This research was aimed to identify the social and economic factors influencing the adoption of integrated pest control using pheromone traps to control the pests on palm trees in four governorates (Babylon, Karbala, Baghdad, and Wasit). The research is conducted with a sample of 340 farmers using of questionnaire. The research conducts the PROBIT model, to evaluate the suitability of the model we used McFadden R2 and Likelihood Ratio-LR test,  Hosmer & Lemeshow goodness of fit test, Wald test to judge the significant correlation. The results showed a significant correlation at 1%, among (age, damage to animals and bees, orchard location, land type and control costs) and at 5% between (education level, return). The study also showed that the degree of risk ranged between 3.4 - 3.5 degrees for chemical pesticides that are used by farmers in the study area for the five environmental categories. The study recommended to implementing the integrated pest control program in the palm sector, the need to increase financial and guidance support for the program because of its positive impact on the social economic aspect of farmers.